Design, Production and Characterization of Peptide Antibodies - Trier, Nicole Hartwig; Houen, Gunnar (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Antibodies are key reagents in diagnostics and experimental biology, capable of detecting numerous antigenic targets. Proteins are often in focus and are usually effective targets for antibody production. Occasionally, however, the native protein is known but not available, or a very specific target is required. In these cases, synthetic peptides, copying essential sequences from the target, are good alternatives for antibody production. Peptide antibodies have been used in diagnostics and experimental biology with great success, especially because they can be produced to multiple targets, for example, native and denatured targets. Traditional peptide antibody proteins encompass animal-based immunization with a synthetic peptide, usually conjugated to a carrier protein to enhance immune presentation, as small peptides tend not to be immunogenic by themselves. There are several strategies for the conjugation of peptides to carriers applied for immunization. This is the most used approach for peptide antibody production. In addition to traditional peptide antibody production, peptide antibodies can be produced using libraries or sequencing. This Special Issue, "Design, Production and Characterization of Peptide Antibodies", aims to describe the current state-of-the-art techniques and characterization/applications within the field as well as new and emerging uses of peptide antibodies.